Penerapan Strategi Everyone Is A Teacher Here Untuk Meningkatkan Aktivitas Dan Hasil Belajar Matematika Pada Siswa Kelas Iv Di Sd Negeri 02 Kemiri Tahun Ajaran 2015/2016 - ERVIAN KRISTIANTO, RENDY, Drs. Saring Marsudi, SH. M.Pd (2016)
Classroom action research (PTK) aims to improve the learning process is not optimal. The real problems that occur in the classroom, especially in mathematics, namely on low activity of learning and student learning outcomes, so this study aims to (1) enhance the learning activities of fourth grade mathematics courses, (2) improving student learning outcomes fourth grade. The study was conducted during two cycles, each cycle two meetings. This type of research is the Classroom Action Research (PTK). Analysis of data using (1) data reduction, (2) Display of data, (3) Verification. Classroom action research conducted at SDN 02 Kemiri by the number of students 20. Based on the results obtained during the study of prasiklus, the first cycle, the second cycle continues to increase. The results obtained based on the indicators of learning activities: (1) activity when asked 15%, 47.5% and 85% (2) activity while answering questions 15%, 40% and 77.5% (3) 35% of activity during the discussion, 67.5% and 95% (4) the current activity to opine 10%, 35% and 75% (5) activity while doing exercises 50%, 77.5% and 97.5% 60.5% The results obtained studying , 74.5% and 86%. Concluded the implementation of the strategy Everyone Here Is A Teacher in math learning can enhance the activity of learning and learning outcomes of fourth grade students of SDN 02 Kemiri 2016.